2019
DOI: 10.1016/j.aeolia.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Examining links between dust deposition and phytoplankton response using ice cores

Abstract: Highlights First study to use contemporary ice core records to explore effect of dust input on primary productivity in High-Nutrient Low-Chlorophyll ocean regions  Investigates event scale and annual scale correlations between dust-Fe and Methanesulfonic acid in the South Atlantic and North Pacific  Results suggest that in spatially defined regions, ice cores may provide high resolution records of dust events and primary productivity response Abstract Dust is a major source of nutrients to remote ocean envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…Indeed, doubling the AIS Fe fluxes in the SOLUB10 experiment increases the C export by only ∼ 3.6 % compared to the SOLUB5 experiment (Table 3). Nevertheless, at a more local scale, the fertilization effect of the AIS induced by global warming could be drastically strengthened, with potentially important consequences for phytoplankton physiology, nutrient availability, and marine ecosystems (Boyd et al, 2010b(Boyd et al, , 2015Hopwood et al, 2017;Boyd, 2019).…”
Section: Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, doubling the AIS Fe fluxes in the SOLUB10 experiment increases the C export by only ∼ 3.6 % compared to the SOLUB5 experiment (Table 3). Nevertheless, at a more local scale, the fertilization effect of the AIS induced by global warming could be drastically strengthened, with potentially important consequences for phytoplankton physiology, nutrient availability, and marine ecosystems (Boyd et al, 2010b(Boyd et al, , 2015Hopwood et al, 2017;Boyd, 2019).…”
Section: Referencesmentioning
confidence: 99%
“…Icebergs and ice shelves contain higher Fe concentrations than seawater (de Baar et al, 1995;Lin et al, 2011;Shaw et al, 2011;Herraiz-Borreguero et al, 2016), mainly as lithogenic material from glacial sediments (Raiswell et al, 2006;Shaw et al, 2011;Hopwood et al, 2017). The melting of icebergs and ice shelves releases Fe to seawater as particulate, dissolved, and potentially dissolvable forms (Raiswell et al, 2008(Raiswell et al, , 2016Hawkings et al, 2014;Herraiz-Borreguero et al, 2016;Hodson et al, 2017), fueling the water column in Fe (Lin et al, 2011;De Jong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral dust and aerosols play an important role in controlling atmospheric radiative forcing and thereby climate variability (IPCC, 2013; Kok et al, 2018). Dust is known as one of the major suppliers of nutrients to global ocean and support phytoplankton productivity and drawdown of atmospheric CO 2 , which have important implications on global climate change (Hooper et al, 2019; Johnson et al, 2011; Martin, 1990). In order to understand past climate variability and changes in the Southern Hemisphere (SH), several studies have been carried out on Antarctic ice core dust records (Delmonte et al, 2002; Delmonte et al, 2013; Delmonte et al, 2019; Laluraj et al, 2014; McConnell et al, 2007; Wegner et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of long range transport is suggested by the observations of recent (spanning last decades) findings of dust in snow of the Antarctica Peninsula (McConnell et al, ; Pereira et al, ) and East Antarctica (Bory et al, ; Laluraj et al, ). Recently, Hooper et al () reported the presence of recent (last decade) deposition of dust in the east flank of a glacier in South Georgia Island directly downwind of Patagonia.…”
Section: Introductionmentioning
confidence: 99%